Pulmonary alveolar proteinosis with peripheral adenocarcinom - Zhang, Ning; Li, Qiaolian; Shao, Changzhou (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Pulmonary alveolar proteinosis (PAP) is a rare interstitial lung disease classified into congenital form, autoimmune form and secondary form. Secondary PAP is caused by underlying conditions including solid malignancies. Few cases reported PAP associated with lung cancers. Objective: To show the clinical features of PAP with adenocarcinom, tried to seek for possible mechanism to explain whole clinical course. Methods: Reported a case of PAP associated with lung adenocarcinom, and also reviewed the relevant literature on PAP. Results: The patient suffered from intermittent cough, fever, shortness of breath, thoracalgia or hemoptysis. Blood gas analysis showed hyoxemia. Spirometric abnormality is mildly restrictive defect. High-resolution computed tomography (HRCT) showed patchy, ground-glass opacities with interlobular septal thickening called as “crazy-paving” pattern. Positron emission tomography/computed tomography (PET/CT) revealed a nodule with characteristics of lobulation and spiculation in the right lung apex section and diffuse consolidation shadow spreading over rest of lung field. Bronchoalveolar lavage fluid (BALF) showed a large amount of amorphous red-dyed materials and a few alveolar macrophages scattered in endoalveolar space with PAS positive. Transbronchial lung biopsy found adenocarcinoma. Wedge resection with mediastinal lymphnode and then 2 cycles of postoperative chemotherapy was carried out. No ground-glass opacities were found in his chest CT pictures in the next nine months. This result may support the theory that lung cancer cells cause quantitative or functional damage to alveolar macrophages, which trend to secondary PAP. Conclusions: The patient had typical clinical features of PAP. PAP may be secondary to lung cancer.